2004
DOI: 10.1111/j.1600-6143.2004.00575.x
|View full text |Cite
|
Sign up to set email alerts
|

Thiopurine S-Methyltransferase Genotype Predicts Azathioprine-Induced Myelotoxicity in Kidney Transplant Recipients

Abstract: Azathioprine (AZA) is an immunosuppressive prodrug that undergoes metabolism by thiopurine Smethyltransferase (TPMT).Eighty to ninety-five percent of low or deficient TPMT enzyme activity is genetically determined by the presence of three nonfunctional mutant alleles: TPMT * 2, TPMT * 3A and TPMT * 3C. Using TPMT as a pharmacogenetic paradigm, we explored the association between these genetic mutations and development of adverse drug effects in an ethnically diverse renal transplant population receiving azathi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 38 publications
1
8
1
Order By: Relevance
“…Similar results were reported by Fabre et al 25 However, in the recently published study, where mean AZA doses for wild-type homozygotes and TPMT variant allele carriers were comparable after 30 days of treatment (2.0 and 1.8 mg/kg per day, respectively), mean values of RBC, HCT, and Hgb were significantly lower in the latter group of patients. 28 In the current study WBC count values were slightly lower in heterozygotes, this difference was most prominent 3 months after transplantation, but even at this time point it did not reach a statistically significant level (P = 0.084).…”
Section: Discussioncontrasting
confidence: 64%
“…Similar results were reported by Fabre et al 25 However, in the recently published study, where mean AZA doses for wild-type homozygotes and TPMT variant allele carriers were comparable after 30 days of treatment (2.0 and 1.8 mg/kg per day, respectively), mean values of RBC, HCT, and Hgb were significantly lower in the latter group of patients. 28 In the current study WBC count values were slightly lower in heterozygotes, this difference was most prominent 3 months after transplantation, but even at this time point it did not reach a statistically significant level (P = 0.084).…”
Section: Discussioncontrasting
confidence: 64%
“…African patients were assessed by McLeod and Siva [123], who reported that the frequency of allelic variants in AZA-treated patients from East and West Africa was similar to that of Caucasians, although all the allelic variants were TPMT*3C. In this sense, Formea et al [124] found that 14.3% of black kidney recipients receiving AZA had the *3C variant.…”
Section: Frequency Of Tpmt Polymorphisms In Differ-ent Populationsmentioning
confidence: 99%
“…For the purpose of this study, leukopenia was defined as white blood cell (WBC) count <3000 cells/mm 3 and thrombocytopenia as platelets (PLT) <100 000/mm 3 . A red blood cell (RBC) count <4 million/mm 3 , haemoglobin (HGB) level <11 g/dL and an haematocrit (HCT) <33% was defined as the threshold for initiating therapy for anaemia (17). Pancytopenia was defined as both RBC and WBC below normal limits.…”
Section: Methodsmentioning
confidence: 99%